Activated carbon becomes active for oxygen reduction and hydrogen evolution reactions. Issue 52 (9th June 2016) - Yan, Xuecheng; Jia, Yi; Odedairo, Taiwo; Zhao, Xiaojun; Jin, Zhao; Zhu, Zhonghua; Yao, Xiangdong
Abstract : A facile defect creation method was used to enable the inert activated carbon into a highly active ORR and HER electrocatalyst. Abstract : We utilized a facile method for creating unique defects in the activated carbon (AC), which makes it highly active for the oxygen reduction reaction (ORR) and hydrogen evolution reaction (HER). The ORR activity of the defective AC (D-AC) is comparable to the commercial Pt/C in alkaline medium, and the D-AC also exhibits excellent HER activity in acidic solution.